The Crime of Recruiting Children into Armed Conflicts and Ways to Combat it - Saeed, Zana Rafiq (Journal of Legal and Political Studies, 2017)
In many armed conflicts, children take a direct role in the fighting, as their role is not limited to the war, many of the boys and girls begin to support functions which already involves particle ban and severe discomfort. They used to carrying heavy loads of ammunition and wounded soldiers, or as messengers and cooks. So the international community has sought through international conventions and treaties to reduce the crime by placing controls on the mechanism and how the participation of children in the fighting and determine the age for recruitment.
Keywords: Armed conflicts; International Convention; recruitment; ammunition